The Legal Authority of Wiretapping by Public Prosecutors in Investigating Corruption Crimes - Ambiya, Aulia Rahman; Malik, Faissal; Rumkel, Nam (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This research aims to analyze the legal authority of public prosecutors to conduct wiretapping in corruption cases and to identify the regulatory weaknesses in the implementation of this authority. The research employs normative legal research, a process used to discover legal rules, legal principles, and legal doctrines to address the legal issues at hand. The normative research approach in this study focuses on three approaches: 1) the statute approach, 2) the conceptual approach, and 3) the comparative approach. The findings indicate that the legal authority of public prosecutors to conduct wiretapping is explicitly stipulated in Article 30C letter (i) of Law No. 11 of 2021, amending Law No. 16 of 2004 on the Prosecutor's Office of the Republic of Indonesia. However, there are several weaknesses in the regulations, including deficiencies in legal substance, legal structure, and legal culture. The weaknesses in legal substance include the absence of specific legislation on wiretapping. The weaknesses in legal structure involve overlapping authority among institutions such as the Prosecutor's Office, BIN, Police, and KPK, as well as the lack of digital forensic laboratories and skilled human resources in wiretapping operations.